Study guide to accompany schewe and smith marketing : concepts and applications - Weber, Robert J.; P.D. Associates; Schewe, Charles D; Smith, Reuben M. (New York : McGraw-Hill Book Company, 1980)
This book is a comprehensive study guide on marketing concepts and applications
Includes Questions & Answers.
kjo 19/01/2019
Loans
Keywords: Marketing